2003
DOI: 10.1016/s1078-5884(03)00343-5
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Popliteal Artery Aneurysms

Abstract: Initial experience with endovascular treatment of the popliteal aneurysm in high-risk patients yielded modest results. Larger number of patients and further follow-up time is necessary to evaluate the long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 14 publications
1
50
0
3
Order By: Relevance
“…3,5,[7][8][9][10][11][12][13][14][15]20,24,[26][27][28][31][32][33][34][35][36][37] In the majority of patients, the endovascular repair was done in the presence of a good tibial run-off; at least two patent tibial arteries were present in 71% (95% CI 65%-76%) of patients. 1,7,10,[12][13][14][15]24,27,32,33,35,38 Several types of stents have been used to treat PAA. At the beginning of the era of this new modality of treatment, in North America home-made devices made of balloon expandable stents covered with vein or PTFE were used, while in Europe the Cragg Endo Pro stents were used, which included the System 1 (a self expandable nitinol stent covered by polyester fabric, Cragg EndoPro System; Mintec, La Ciotat, France); the Passager stent graft (a self expandable, polyester-covered metal stent-grafts; Boston Scientific, Watertown, Mass), and the Corvita stentgraft (a metallic self-expandable, braided wire stent to which is bonded an inner liner of polycarbonate urethane microfibers; Boston Scientific, Bülach, Switzerland).…”
Section: Resultsmentioning
confidence: 99%
“…3,5,[7][8][9][10][11][12][13][14][15]20,24,[26][27][28][31][32][33][34][35][36][37] In the majority of patients, the endovascular repair was done in the presence of a good tibial run-off; at least two patent tibial arteries were present in 71% (95% CI 65%-76%) of patients. 1,7,10,[12][13][14][15]24,27,32,33,35,38 Several types of stents have been used to treat PAA. At the beginning of the era of this new modality of treatment, in North America home-made devices made of balloon expandable stents covered with vein or PTFE were used, while in Europe the Cragg Endo Pro stents were used, which included the System 1 (a self expandable nitinol stent covered by polyester fabric, Cragg EndoPro System; Mintec, La Ciotat, France); the Passager stent graft (a self expandable, polyester-covered metal stent-grafts; Boston Scientific, Watertown, Mass), and the Corvita stentgraft (a metallic self-expandable, braided wire stent to which is bonded an inner liner of polycarbonate urethane microfibers; Boston Scientific, Bülach, Switzerland).…”
Section: Resultsmentioning
confidence: 99%
“…25 In this early series, 11 patients had a total of 12 PAAs treated with covered stents. At 1 and 12 months, these investigators observed 47% primary patency and 75% secondary patency rates.…”
Section: Open Repair Remains the Gold Standard (Dr Randy Moore)mentioning
confidence: 99%
“…Both grafts have been used to treat PAA, and various groups of investigators have published their results. [2][3][4][5][6][7][8][9] A recent meta-analysis compared endovascular repair of PAA with open surgery and included 3 studies and 141 patients (37 endovascular, 104 open). 10 The authors concluded that the main advantage of endovascular repair was a shorter hospital length of stay, with a weighted mean difference of Ϫ3.9 days in favor of endovascular repair.…”
mentioning
confidence: 99%